Qualitative evaluation of the contribution of CanMEDS roles in the development of area of focused competence diplomas - Agarwal, Tanvi; Conejero Muller, Maria Jose; Atkinson, Adelle; Bismilla, Zia (Canadian Medical Education Journal, 2023)
Background: While many Area of Focused Competency (AFC) Diplomas are available to those who have completed Pediatric residency training, it is not known which competencies are enhanced within each AFC discipline. Our objective was to determine which CanMEDS roles were targeted by existing AFCs available to those who have completed Pediatric residency training and identify gaps within CanMEDs roles that may be fulfilled by the development of new AFCs. Methods: A qualitative study was undertaken using document analysis methodology to compare CanMEDS competencies across AFCs available to those with Royal College examination eligibility or certification in Pediatrics. RCPSC Competency Training Requirements documents were used to compare and contrast the competencies in each AFC with competencies established in Pediatric residency training. Key and Enabling Competencies were compared for each CanMEDS role to identify differences. Results: Ten AFCs were identified with eligibility requirements including Royal College examination eligibility or certification in Pediatrics. All 10 AFCs included at least one new Medical Expert competency, for a total of 42 unique competencies in this role across all AFCs. The Scholar role had only 10 new competencies across seven AFCs, while only one AFC added a single unique competency in the Collaborator role. Conclusions: The majority of new competencies contributed by AFCs lie within the CanMEDS role of Medical Expert. The Scholar and Collaborator roles have the least differences when comparing competencies of existing AFCs to those competencies established in Pediatric residency training. Developing additional AFCs that offer advanced skills in these roles may help close this gap within the discipline of Pediatrics.